Program Administrasi Persuratan Pada Desa Parakanmulya Kecamatan Tirtamulya Karawang - Surtika Ayumida; Ardiansyah, Dian; Supriyatna (PROFITABILITAS, 2022)
The development of information and communication technology at this time has accelerated and changed the pattern of human work to be faster, more effective and efficient. This progress encourages the restoration of the administrative service system in accordance with the development of information technology, so that the data management system runs better and safer. Thus the information system can assist in improving the quality of information and efficiency in public services. In Parakanmulya village, most of the correspondence services are still carried out conventionally, namely with word processing applications (Ms. Word), so the process takes longer, to document letter files is not well administered, errors often occur and even archives are lost due to the large number of archives . Seeing this situation, it is appropriate for the government to use the computer advancement side to support performance to be more efficient in order to improve services to the community by switching from a system that currently still uses bookkeeping media to a computerized information system.